Predicting Corporate Failure in Malaysia: An Application of the Logit Model to Financial Ratio Analysis - Mohamed Sulaiman,; Ang Ji Li,; Ahmadu Umaru Sanda, (Asian Academy of Management Journal, 2001)
A logit model that distinguishes between Malaysian firms that did and those that did not seek for court protection from their creditors is tested empirically in this research. Three factors were found to have significant discriminating power ; debt, ratio, interest coverage, and total assets turnover . The logit model was able to classify accurately 80.7 per cent of the firms in the estimation sample and 74.4 per cent in the hold out sample.